Relationship between quality of life indicators and cardiac status indicators in chemotherapy patients - Geršak Blaž Matija; Kukec Andreja; Steen Henning; Montenbruck Moritz; Šoštarič Maja; Schwarz Arne Kristian; Esch Sebastian; Kelle Sebastian; Giusca Sorin; Korosoglou Grigorios; Wülfing Pia; Dent Susan; et al. (Sciendo, 2021)
With the aim of improving personalized treatment of patients on chemotherapy, the objective of the study was to assess the degree of association between selected Quality of life (QoL) indicators and both clinical and imaging cardiac status indicators when detecting deterioration in QoL of these patients.